Autophagic processes of normal and malignant metabolic pathways - Aurelian Udristioiu* and Manole Cojocaru (African Journal of Biological Sciences, 2019)
Autophagy is a cellular process that maintains the homeostasis of the normal cell, but autophagic dysfunction is associated with human diseases, such as cancer. In normal cells, the initial signal to form auto-phagosomes is by the class III phosphatidyl-inositol (PI) 3 kinase complex consisting of sequence genes, Beclin1/Atg6 and class III PI3K (Vps34). This process is negatively regulated by binding of Bcl-2 family members such as Bcl-xL to Beclin1 preventing Beclin1 binding to the PI3K-III complex and thereby reducing autophagy. In cancer, the autophagy can be neutral, tumor-suppressive, or tumor-promoting in different contexts. Genomic analysis of human cancers indicates that the loss or mutation of core autophagy Atg genes, whereas oncogenic events that activate autophagy and lysosomal biogenesis have been identified in malignant diseases. Optimal combination of inductors or inhibitors of autophagy with chemo or radiotherapy in a variety of tumor type, in different phases, can be successful approaches for improve the effect of anticancer therapies.
Keywords: Autophagy, Apoptosis, Bcl-2-protein, Phosphatidyl-inositol (PI) 3 kinase complex, Mammalian target of rapamycin (mTOR), Tensin-homologous phosphatase (PTEN).